Predictors of treatment delay among drug resistant tuberculosis patients in Uganda - Nabukenya Diana Kasozi; Lwanga Charles; Asiimwe JohnBosco; Luzze Henry (BMC Infectious Diseases)
Abstract Background Drug resistant tuberculosis (DR-TB) continues to be a significant global public health concern despite the availability of effective TB medicines. Equally, delayed DR-TB treatment initiation is associated with increased morbidity, amplified resistance, transmission risk and poor treatment outcomes. This study aimed to investigate treatment delays and identify predictors of delayed treatment initiation among DR-TB patients in Uganda. Method A retrospective study was conducted using routine DR-TB national case registration data between January 2012 and December 2019. Stata version 15 was used to run uni-variate analysis to describe patient characteristics using frequencies and percentages; bivariate analysis to identify significant differences in median times to treatment initiation; and logistic regression model was fitted, and adjusted odds ratio (AOR) with 95% confidence interval was used to identify factors associated with DR-TB treatment delay. Results A total of 2,166 DR-TB patients were included in this study. The median treatment initiation delay was 10 days. Approximately 57% of DR-TB patients experienced delays in starting their treatment beyond the acceptable 7-day timeframe. Being diagnosed as RR-TB [AOR = 1.22; 95% CI: 1.08–1.37], and being a recurrent TB patient [AOR = 1.22; 95% CI: 1.01–1.47] were associated with treatment delays. Patients with previous history of ‘lost to follow-up’ (LTFU), failure and being diagnosed as Pre-XDR-TB were less inclined to delay DR-TB treatment. Conclusion Several DR-TB patients experienced treatment delay. The delay was significant among patients diagnosed as RR-TB and those with TB treatment history of recurrent TB. This highlights the need for heightened vigilance among healthcare workers when managing DR-TB patients with a history of past TB treatment and those diagnosed as RR-TB to minimize delays. Furthermore, future research should investigate a comprehensive list of variables influencing the timing of treatment initiation after diagnosis. An in-depth understanding of the effects of these factors can inform targeted interventions to optimize treatment strategies for improved DR-TB patient outcomes.